Bone marrow involvement in a patient with alpha heavy chain disease:Response to tetracycline treatment - Zahit Bolaman (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
A 28-year-old man admitted with abdominal pain, weight loss and diarrhea. Barium x-ray studies showed segmentation, dilatation of bowel loops, mucosal folds thickening and delayed intestinal transit. Biopsy specimens histologically revelaed villous atrophy and plasmacytic infiltration limited to mucosa and submucosa. Computed tomography showed multiple lymphadenopathy in the abdomen. Serum protein electropheresis and immunoelectropheresis indicated elevated IgA concentration. Bone marrow aspiration and biopsy revealed presence of lymphoplasmacytic infiltration. Immunohistochemical analysis of the intestine, lymph node showed positivity for CD45, CD-79, CD-20.  After tetracycline treatment the patient’s symptoms, abdominal lymphadenopathy and bone marrow infiltration disappeared and IgA concentration was normalized.